PHONETIC DESCRIPTION OF THE IANGUAGE OF MIGRANI'S PROM AYACUCHO IN LIMA - Mendoza Cuba, Aida (2009)
Through the observarían of the language of migrants from Ayacucho living in Lima,one may find that many phonetic traits characteristic of their mother tongue are tOundin the segmental level and in the suprasegmental level as well. Specially the rhythmand intonation in Spanish seem to reflect the same segmentation and timing coming from Quechua's prosody. All these facrs reveal, at the same time, different stages ofacquisition of the second language.